2004
DOI: 10.1002/cpp.412
|View full text |Cite
|
Sign up to set email alerts
|

The Glasgow Social Self‐Efficacy Scale—a new scale for measuring social self‐efficacy in people with intellectual disability

Abstract: This paper describes the development of the Glasgow Social SelfEfficacy Scale (GSSES) and reports preliminary details of its psychometric properties.The scale was found to have a test-retest reliability correlation coefficient of 0.90 in a sample of participants with intellectual disability. This represents strong test-retest reliability. Cronbach's a for internal reliability of GSSES was 0.78 for the 38 participants with intellectual disability and 0.90 for the 19 participants in the non-disabled group, repre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
16
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 24 publications
2
16
0
Order By: Relevance
“…Gilmore and colleagues (2013) also examined the influence of gender on the RSCA scores and found no significant differences except that girls reported higher sensitivity than boys. With regard to individual qualities in the sense of mastery domain, the obtained results are in accordance with the findings of other authors indicating that there were no significant gender differences in self-efficacy in persons with ID (Gresham et al, 1988;Payne & Jahoda, 2004). Nota and associates (2010) explained the lack of differences in self-efficacy beliefs in male and female persons with ID by the fact that school and extra scholastic activities for individuals with ID were rarely differentiated by gender, and thus girls and boys with ID mainly had similar experiences.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Gilmore and colleagues (2013) also examined the influence of gender on the RSCA scores and found no significant differences except that girls reported higher sensitivity than boys. With regard to individual qualities in the sense of mastery domain, the obtained results are in accordance with the findings of other authors indicating that there were no significant gender differences in self-efficacy in persons with ID (Gresham et al, 1988;Payne & Jahoda, 2004). Nota and associates (2010) explained the lack of differences in self-efficacy beliefs in male and female persons with ID by the fact that school and extra scholastic activities for individuals with ID were rarely differentiated by gender, and thus girls and boys with ID mainly had similar experiences.…”
Section: Discussionsupporting
confidence: 91%
“…In a meta-analytic review of studies on self-serving attributional bias, Mezulis and colleagues (2004) concluded that, in the general population, the level of positivity bias in attributions was the lowest in early adolescence (12-14 years of age) when a person starts realizing that frequent failures can be the result of lower abilities. The obtained findings indicating the absence of significant age differences in self-efficacy are supported by the results of previous studies (Gresham et al, 1988;Payne & Jahoda, 2004). Similarly, the results which refer to sense of relatedness are consistent with the findings of other authors according to which, in persons with ID, there were no significant age differences in social skills (Adeniyi & Omigbodun, 2016;Heiman & Margalit, 1998), peer acceptance and relations (Heiman & Margalit, 1998;Wendelborg & Kvello, 2010), and perceived social support (Lunsky & Benson, 2001).…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, this was included as an exploratory variable, although it seems unlikely that enough participants would have such experience as to warrant statistical attention. This line of inquiry also shows no relation between social self-efficacy versus others' ratings of actual social skills in a sample of individuals with intellectual disabilities (Payne & Jahoda, 2004 …”
Section: Witness Self-efficacy and Outcome Indicatorsmentioning
confidence: 87%
“…The few studies that have investigated social skills in an ID population have shown a relation between poor verbal and nonverbal social skills and depressive symptoms in samples of adults with borderline IQ to moderate ID (Benson, Reiss, Smith, & Laman, 1985; Heiman & Margalit, 1998; Helsel & Matson, 1988; Laman & Reiss, 1987; Payne & Jahoda, 2004; Reiss & Benson, 1985). However, conclusions from these studies are limited in that they largely included participants who did not have a diagnosis of depression, and thus results do not reflect whether adults with mild ID diagnosed with depression exhibit a unique profile of maladaptive social skills.…”
mentioning
confidence: 99%